Perioperative antibiotic prophylaxis in an Australian burns unit - Patrick Lu; Dane Holden; Alex Padiglione; Heather Cleland (Australasian Journal of Plastic Surgery)
**Background** Perioperative antibiotic prophylaxis is perceived to reduce intraoperative bacteraemia and prevent surgical site infections, however, the evidence for its use in burns surgery is limited. Excessive use of perioperative antibiotics has become a growing concern. The authors aimed to audit the prescribing practices of perioperative antibiotic prophylaxis at the Victorian Adult Burns Service and determine whether the duration of antibiotic prophylaxis influenced the risk of postoperative wound infection, bacteraemia and antibiotic resistance.